Theoretical analysis of semi-active noise control - Thomas Kletschkowski (Akustika, 2021)
Abstract: A significant reduction of disturbing noise can be achieved by passive, semi-active and fully active control approaches. Passive noise treatments such as dynamic vibration absorber are very robust and can be applied to obtain a broadband performance. Active noise control systems are designed to control harmonic or broadband noise. They are very effective, if the control volume is small as known from single-input/single-output systems used in active headphones. However, if distributed control is required, the control profit is not scalable, because the required multiple-input/multiple-output systems must be adjusted to specific acoustic modes as known from the active control of propeller-aircraft interior noise. Semi-active control that is based on the principle of dissipation allows to combine several single-input/single-output systems without coupling. Thus semi-active approaches are capable to solve the problem of scalability. The present paper reports on a specific approach that is based on a dynamic absorber attached to a vibrating structure and coupled with a dissipating electrical network. The electrical components of this network can be adjusted to the mechanical impedance to realize dissipation. To focus on the performance principle, the theoretical investigations are presented in a dimensionless analysis.
Keywords: Semi-active control; vibration absorber; dissipative network